2015
DOI: 10.1111/crj.12364
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, dose‐finding trial of ghrelin treatment for chronic respiratory failure

Abstract: Although the primary outcome of the study was not met, high-dose ghrelin with PR improved exertional cardiac function and blood gas values, and inhibited circulating VEGF-A levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Kodama and colleagues showed ghrelin to suppress airway inflammation and increase functional exertion capacity in patients with chronic respiratory failure [73]. Miki and colleagues later showed that ghrelin enhanced exercise capacity, expiratory pressure and improved respiratory symptoms in COPD patients [83,243] and showed benefits on exertional dyspnea [244], These effects may be dose-dependent [245,246]. For lung cancer, treatment with the potent ghrelin analog anamorelin has shown benefits on appetite, lean mass retention, performance and quality of life [133,134,135].…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…Kodama and colleagues showed ghrelin to suppress airway inflammation and increase functional exertion capacity in patients with chronic respiratory failure [73]. Miki and colleagues later showed that ghrelin enhanced exercise capacity, expiratory pressure and improved respiratory symptoms in COPD patients [83,243] and showed benefits on exertional dyspnea [244], These effects may be dose-dependent [245,246]. For lung cancer, treatment with the potent ghrelin analog anamorelin has shown benefits on appetite, lean mass retention, performance and quality of life [133,134,135].…”
Section: Pulmonary Diseasementioning
confidence: 99%
“… 24 Recently, Miki and his colleagues further performed a multicenter, randomized, double-blind, placebo-controlled trail, indicating underweight COPD patients benefited from intravenous treatment of high-dose ghrelin (2 µg/kg) twice daily for 3 weeks with improvements in St. George Respiratory Questionnaire score, exercise capacity, ventilatory–cardiac parameters, and exertional cardiac function. 25 28 These data further suggest that compensation with exogenous ghrelin may be a potential choice in treatment of underweight COPD patients.…”
Section: Discussionmentioning
confidence: 83%
“…63,64 In humans, multiple clinical trials for ghrelin have been completed for several disorders, including heart diseases, chronic respiratory failure, weight loss, and inflammation. [65][66][67][68] Exogenous ghrelin treatment significantly suppresses endoplasmic reticulum stress and inflammation-induced testicular dysfunction by regulating the toll-like receptor 4 (TLR4)/ NF-κB signaling pathway in male mice. 69 According to F I G U R E 1 Post-translational processing of ghrelin.…”
Section: Direct Effects Of the Ghrelin Pathway On Inflammation Regula...mentioning
confidence: 99%
“…In vivo, exogenous ghrelin administration prevents cerulein‐induced acute pancreatitis in rats by alleviating pancreatic blood flow; reducing inflammatory factors TNF‐α and interleukin‐1β (IL‐1β); activating IKKβ/NF‐κB signaling, and stimulating pancreatic cell regeneration 63,64 . In humans, multiple clinical trials for ghrelin have been completed for several disorders, including heart diseases, chronic respiratory failure, weight loss, and inflammation 65–68 . Exogenous ghrelin treatment significantly suppresses endoplasmic reticulum stress and inflammation‐induced testicular dysfunction by regulating the toll‐like receptor 4 (TLR4)/NF‐κB signaling pathway in male mice 69 .…”
Section: Direct Effects Of the Ghrelin Pathway On Inflammation Regula...mentioning
confidence: 99%